Video Matting Using Motion Extended GrabCut. - CORRIGAN, DAVID; KOKARAM, ANIL CHRISTOPHER (IEEE, 2008)
GrabCut is perhaps the most powerful semi-automatic algorithm for matting presented to date. In its existing form, it is not suitable for video object segmentation. This paper considers major extensions that make it suitable for this purpose. A method for initialising matting without user intervention is presented, followed by a more robust data model using a Mean Shift algorithm to control model complexity. In addition, normalised motion information as well as colour is used to form joint colour and motion feature vectors. This improves the robustness of the mattes in the presence of colour camouflage and decreases the user intervention required for a successful result. Comparison between GrabCut and the proposed Motion Extended GrabCut (MxGrabCut), shows the improvement for video matting.
IET European Conference on Visual Media Production (CVMP)
PUBLISHED
London, UK.
Keywords: Foreground Segmentation, Compositing, Parametric Data Modelling, Global and Local Motion Estimation, Digital Cinema Post Production.